Investigation of Bleeding Disorders: When and How Should We Test Platelet Functions? - Gresele, Paolo; Falcinelli, Emanuela; Bury, Loredana (Hämostaseologie, 2025)
Inherited platelet disorders (IPDs) are rare conditions with diverse underlying pathophysiology which should be suspected in patients presenting with mucocutaneous bleeding or hemorrhages upon hemostatic challenges, in the presence or not of thrombocytopenia. Identifying IPDs is critical for providing appropriate care, preventing misdiagnosis, and avoiding unnecessary interventions, such as splenectomy. Syndromic IPDs, which may be associated with severe complications like kidney failure, infection, and malignancies, underscore the importance of accurate diagnosis and tailored management.Diagnosing IPDs remains challenging, requiring a comprehensive approach that integrates clinical assessment, evaluation of the bleeding history using standardized tools, like the ISTH-BAT, and first-line laboratory tests, such as light transmission aggregometry and flow cytometry. Second-line and specialized tests, including transmission electron microscopy, genetic analysis, and biochemical studies, may provide further insight in complex cases. Technological advancements, including multicolor flow cytometry and microfluidic tools, may in perspective improve IPD diagnostics by providing high-throughput and precise laboratory assays. In particular, mass cytometry and multi-omics may contribute to unraveling IPD pathophysiology, identifying novel markers, and refining disease classification. The application of artificial intelligence shows potential for improving diagnostic accuracy through the automated analysis of platelet morphology and function, from flow cytometry and digital microscopy assays, and for improving the understanding of pathogenic mechanisms of IPD through the examination of big data.This review summarizes current IPD platelet function testing strategies, emphasizing the need for a structured, tiered approach and examining emerging technologies and AI applications that could revolutionize diagnostic workflows, leading to personalized care and to an expanded understanding of IPDs.
Keywords: flow cytometry; inherited platelet function disorders; light transmission aggregometry